Study on formation and migration of emulsions in porous media during chemical flooding of heavy oil - MA Tao; XIAO Pufu; TANG Liang; LUN Zengmin; TANG Yongqiang; ZHOU Bing (Youqi dizhi yu caishoulu, 2024)
Emulsification is one of the main mechanisms of chemical flooding to enhance oil recovery in heavy oil reservoirs. The emulsification of heavy oil in porous media is closely related to reservoir temperature and oil-displacing agent concentration. The relationship between the critical concentration and temperature of the oil-displacing agent required to form oil in water （O/W） emulsions in heavy oil was studied by emulsification experiment. The emulsification and migration rules of crude oil during chemical flooding of heavy oil were studied by using high-temperature and high-pressure microscopic visual oil displacement devices. The results show that a higher temperature in the emulsification experiment indicates that the crude oil is easier to emulsify， and the critical emulsification concentration of the required oil-displacing agent is lower. The critical emulsification concentration decreases by 90% when the temperature increases from 30 °C to 90 °C during the experiment. There are three modes of emulsification of heavy oil in porous media during microscopic oil displacement experiments for chemical flooding of heavy oil： the emulsification mode of heavy oil shows dispersion， migration， and coalescence at the throat in porous media when the concentration of the oil-displacing agent is less than the critical emulsification concentration of the oil-displacing agent required for heavy oil emulsification at this temperature； the emulsification mode of heavy oil indicates emulsification， migration， re-emulsification， and re-migration when the concentration of the oil-displacing agent is greater than the critical emulsification concentration of the oil-displacing agent required for heavy oil emulsification at this temperature； the emulsification mode of heavy oil is manifested as contact， stripping， and migration when the concentration of the oil-displacing agent is much larger than the critical emulsification concentration of the oil-displacing agent required for heavy oil emulsification at this temperature. Therefore， the concentration of the oil-displacing agent should be increased as much as possible to achieve efficient emulsification of heavy oil and improve oil recovery under the premise of controlling the cost when chemical flooding of heavy oil is carried out.